Associations of Helicobacter pylori infection and chronic atrophic gastritis with accelerated epigenetic ageing in older adults - Gao, Xu; Zhang, Yan; Brenner, Hermann (British journal of cancer, 2017)
Background: Helicobacter pylori (HP) infection and chronic atrophic gastritis (CAG) have shown strong associations with the development of gastric cancer. This study aimed to examine whether both risk factors are associated with accelerated epigenetic ageing, as determined by the ‘DNA methylation age’, in a population-based study of older adults (n=1477). Methods: Serological measurements of HP antibodies and pepsinogen I and II for CAG definition were obtained by ELISA kits. Whole blood DNA methylation profiles were measured by Illumina Human Methylation450K Beadchip. DNA methylation ages were calculated by two algorithms proposed by Horvath and Hannum et al. Results: After adjusting for potential covariates in linear regression models, we found that HP infection, infection with virulent HP strains (CagA+) and severe CAG were significantly associated with an increase in DNA methylation age by ~0.4, 0.6 and 1 year (all P-values <0.05), respectively. Conclusions: Our study indicates that both CagA+ HP infection and CAG go along with accelerated epigenetic ageing.